Drainage network extraction using LiDAR-derived DEM in volcanic plains. - Liu, Xiaoye; Zhang, Zhenyu (Area, 2011)
A study used airborne light detection and ranging (LiDAR) to generate the high-accuracy and high-resolution digital elevation models (DEMs) that are a prerequisite to the automatic extraction of drainage networks over low-relief terrains. Drainage network extraction was performed on two sub-catchments on the western Victorian Volcanic Plains in Australia. Drainage networks and some parameters describing drainage network composition, including the stream orders, the numbers of streams, and the stream lengths, were derived from both the LiDAR DEM and the statewide Vicmap 20-meter resolution DEM, dating from the 1990s. Findings revealed that the LiDAR-derived DEM offers significantly more detail, especially for delineating low-order stream, or headwater, segments in sub-catchments of low-relief terrain.